Dynamic Student Feedback Management System Using PHP (Tech Feed) - -, A Nalini; -, M Nadeesh; -, C Niranjan; -, P Nishanth (International Journal For Multidisciplinary Research, 2024)
Tech Feed is a comprehensive and efficient student feedback system designed for educational institutions. It utilizes rating scales, multiple-choice questions, open-ended responses, and comment boxes to capture diverse student perspectives. Upon submission, the system automatically collates and organizes the data, generating reports and analytics accessible to administrators, faculty members, and department heads. This enables stakeholders to identify strengths and weaknesses in their programs and teaching methodologies. Feedback is categorized into levels such as very good, good, average, below average, and needs improvement. The system features a unified feedback form for all subject faculties, streamlining the process for students. Additionally, Tech Feed includes specialized feedback systems for guest lectures and industrial visits, allowing students to provide valuable insights and suggestions. This facilitates the improvement of future events and enhances the overall learning experience. By transitioning from paper-based to online feedback, Tech Feed significantly accelerates the feedback process